Anti-Tumoral Effects of a (1H-Pyrrol-1-yl)Methyl-1H-Benzoimidazole Carbamate Ester Derivative on Head and Neck Squamous Carcinoma Cell Lines - Alice Nicolai; Valentina Noemi Madia; Antonella Messore; Daniela De Vita; Alessandro De Leo; Davide Ialongo; Valeria Tudino; Elisabetta Tortorella; Luigi Scipione; Samanta Taurone; Tiziano Pergolizzi; Marco Artico; et al. (MDPI AG, 2021)
Nocodazole is an antineoplastic agent that exerts its effects by depolymerizing microtubules. Herein we report a structural analog of nocodazole, a (1H-pyrrol-1-yl)methyl-1H-benzoimidazole carbamate ester derivative, named RDS 60. We evaluated the antineoplastic properties of RDS 60 in two human head and neck squamous cell carcinoma (HNSCC) cell lines and we found that this compound significantly inhibited replication of both HNSCC cell lines without inducing any important cytotoxic effect on human dermal fibroblasts and human keratinocytes. The treatment of HNSCC cell lines with 1 μM RDS 60 for 24 h stopped development of normal bipolar mitotic spindles and, at the same time, blocked the cell cycle in G2/M phase together with cytoplasmic accumulation of cyclin B1. Consequently, treatment with 2 μM RDS 60 for 24 h induced the activation of apoptosis in both HNSCC cell lines. Additionally, RDS 60 was able to reverse the epithelial-mesenchymal transition and to inhibit cell migration and extracellular matrix infiltration of both HNSCC cell lines. The reported results demonstrate that this compound has a potent effect in blocking cell cycle, inducing apoptosis and inhibiting cell motility and stromal invasion of HNSCC cell lines. Therefore, the ability of RDS 60 to attenuate the malignancy of tumor cells suggests its potential role as an interesting and powerful tool for new approaches in treating HNSCC.